Developing a measurement of employee learning agility. Issue 5 (8th June 2021) - Lee, Jinju; Song, Ji Hoon
Abstract : Purpose: The purpose of this study is to develop a reliable and valid measurement of employee learning agility for use in human resources development. Design/methodology/approach: This paper analyzed a total of 365 cases collected from Korean organizations. This paper conducted exploratory factor analysis, confirmatory factor analysis and Rasch analysis to validate the measurement. This paper conducted a measurement invariance (MI) test to confirm the generalizability of the measurement and used Harman's single factor test to assess the common method variance (CMV). Findings: This paper derived a learning agility measurement with six subfactors (Cronbach's α = 0.893). This paper verified that it could be applied equally to supervisors and subordinates using an MI test. Factor analysis confirmed the feasibility of CMV. Based on I-ADAPT theory, the learning agility measurement can be applied to assess not only leader competency but also general employee competency. Research limitations/implications: Practitioners may use this model of learning agility for developing competency-based training programs and evaluations. This study is meaningful because it extends the concept of learning agility. In particular, the MI test indicated that there are no differences between supervisors and employees regarding the utility of the concept. Originality/value: This study is meaningful because it extends the concept of learning agility. In particular, the MI test indicated that there are no differences between supervisors and employees regarding the utility of the concept. The concept in this paper is distinguished from other studies by applying the Rasch model from an item response theory perspective.